Sustainability Bisnis Cafe di Kota Mataram: Persfektif Pelanggan (Studi Kasus Pada Acibara Coffee) - Winoto, Muhammad Bimo; Isnawati (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the implementation of business sustainability at Acibara Coffee in Mataram City from a customer perspective. The method used is descriptive qualitative with observation, interview, and documentation techniques. The informants of this study are customers. The results of the study indicate that Acibara Coffee remains optimistic and sustainable in the coming years when viewed from a customer perspective. Overall, the business sustainability implemented by Acibara is considered capable of strengthening customer loyalty and business competitiveness in a sustainable manner. Overall, the business sustainability implemented by Acibara is considered capable of strengthening customer loyalty and business competitiveness in a sustainable manner.